Hubungan Depresi Dengan Lama Pemenuhan Kebutuhan Tidur Pada Lansia Di Desa Mojokambang Bandarkedungmulyo Jombang - Manzilatil Ilya (MEDICA MAJAPAHIT, 2012)
One of changes happened to elderly is change of sleep pattern. Cause of sleep disorder on elderly is depression. Research goal is to know relation between depression and time period of sleeping needÂ accomplishment on elderly in Mojokambang village, Bandarkedungmulyo, Jombang. The research design is analytic with crossectional approach. Independent variable is depression and dependent variable is time period of sleeping needÂ accomplishment. The populations are 86 people and samples are 70 people, with sampling random simpel technique analysis is pearson test with alfa 0,05. Based on research, known that (1) most elderly experience of heavy depressionÂ and there isÂ no one experience of light orÂ heavy depression. (2) Most of elderly have time period of sleeping needÂ accomplishment around 1-6 hours/dayÂ and no lansia needs less than 1 hour/day. Result of research express that by pearson test, get P Value value is 0,000, whileÂ value Î± is 0,05. because of P Value so a Ho refused but H1 accepted, it means there is relation/between depression with have time period of sleeping need accomplishment on elderly in Countryside Mojokambang Bandarkedungmulyo Jombang. Â These felling are physiologically stimulates the sensory system to tge midbrain level in formatio reticularis area, this state will instead stimulate the cerebral cortex and peripheral nervous system, subsequent reciprocal signals from the two areas will return to the reticular activation system, so that the system is still avtive or in other side elderly will know the state of siege or can not sleep. The factor that effect depression in the elderly are the economic status factor, and job beside factors other than emplyment or economic, depression is also influenced by education and merried status factor. Based onÂ result of above research suggested to health providersÂ toÂ optomalize the counselling about theÂ importantance of accomplishmen of sleep need and minimizeÂ Â depressionÂ , spreadsÂ leaflet and involvesa health cadre of elderlyÂ in giving motivation and education for elderlyÂ to get in Comprehensive Service Post forÂ elderly regularly.